The Da'wah Method of Kiyai Haji Muhammad Rahmat Najieb in the Context of Reform - Muhammad Mufti Sulthanan Nasira (Journal Of Social Science (JoSS), 2025)
This study aims to analyze the da'wah methods of al-hikmah, mauidzhah hasanah, and al-mujaadalah used by KH. Muhammad Rahmat Najieb in the context of Islamic renewal (tajdid) at the PP Persis Mosque. The research uses a qualitative descriptive approach with data collection techniques through interviews, observation, and documentation. The results show that KH. Muhammad Rahmat Najieb, as a productive scholar in "bil kitabah" da'wah, implements the al-hikmah method through precise textual-contextual word selection, mauidzhah hasanah through logic-based advice and storytelling (qishah), and al-mujaadalah through critical yet polite scientific discussions. The significance of this research reveals that his primary audience consists of asatidz and da'wah practitioners from various regions, making his method a high-level model for intellectual transmission. This study concludes that the integration of these three methods is effective in communicating moderate renewal ideas while maintaining the principles of Islamic purification.